2022
DOI: 10.17309/tmfv.2022.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vinyasa Training on Dynamic Body Balance of Male National Level Yoga Players

Abstract: Background. Body balance is among the most important aspects for achieving athletic excellence in competitive sports. Body balance helps in the development of proper body posture control, which supports high performance and skill demonstration across all sports. Body balance is known to be positively correlated to competitive athletic performance. In sports, good balance implies moving more efficiently and with better body control. Yoga is one of the means of improving body balance, and it has also been linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…In reality, it is well recognised that when a new stimulus is used as a training intervention, the greatest advantage can be obtained. Previous research has also revealed efficacy of a 6-week Vinyasa Yoga Training Programme (VYTP) in improving dynamic body balance of male national level yoga players and it was observed that the male national yoga players had a substantial difference in dynamic body balance compared to the control group (Singh et al, 2022) and in other study it was found (Singh, et al, 2015) that an 8-week yoga training programme had a substantial impact on female hockey players' physical strength, endurance, flexibility, and agility. According to (Hosseini et al, 2018), prescription regular exercise regimens with controlled intensity and time, particularly resistance training and hatha yoga training, can enhance lower limb strength and balance in multiple sclerosis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, it is well recognised that when a new stimulus is used as a training intervention, the greatest advantage can be obtained. Previous research has also revealed efficacy of a 6-week Vinyasa Yoga Training Programme (VYTP) in improving dynamic body balance of male national level yoga players and it was observed that the male national yoga players had a substantial difference in dynamic body balance compared to the control group (Singh et al, 2022) and in other study it was found (Singh, et al, 2015) that an 8-week yoga training programme had a substantial impact on female hockey players' physical strength, endurance, flexibility, and agility. According to (Hosseini et al, 2018), prescription regular exercise regimens with controlled intensity and time, particularly resistance training and hatha yoga training, can enhance lower limb strength and balance in multiple sclerosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…One should pay close attention to their breathing rhythm while practising vinyasa. Many research have demonstrated that practising yoga improves a number of both psychological and physical aspects (Singh et al, 2022). Vinyasa yoga, a style of Hatha yoga that places an emphasis on systematic practise (Beth et al, 2012) In essence, it is a powerful form built on a fast flow of sun salutations that are timed with breath.…”
Section: Introductionmentioning
confidence: 99%
“…27 , 28 According to current research findings, experts (Jones et al , 2002) contend that the factors that determine mental toughness are mostly inherited as well as learnt, experienced, and environmental factors. 29 Greater mental toughness has been linked to stronger physical and cognitive skills, as well as self-esteem, in numerous studies. 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“… 29 Greater mental toughness has been linked to stronger physical and cognitive skills, as well as self-esteem, in numerous studies. 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…It is a moksha shastra in this sense, a teaching that leads to a progressive release from the various types of human suffering (Connolly, 2007) [2] . The Sanskrit verb "YUJ" i.e., "to join" or "to yoke" is where the word "yoga" originates (to combine) [3] . It represents the idea of integrating the body, mind, and spirit of the self while also tying oneself to discipline.…”
Section: Introductionmentioning
confidence: 99%